Scaling behavior of a wormlike polyelectrolyte chain by mesoscopic Brownian dynamics simulations - Chun, Myung-Suk (SPRINGER, 2010)
The scaling prediction of semiflexible wormlike chain was examined by applying Brownian dynamics simulation, which goes beyond other simulations as they do not consider both the hydrodynamic interaction between pairs of beads and long-range screening effect. The rheological behavior of the intrinsic viscosity was properly implemented by combining with optimized model parameters for the polyelectrolyte xanthan, and the validity of the simulation was previously confirmed. Scaling plots present that the structure and diffusion of polyelectrolyte chains depend sensitively on the Debye screening effect. In the scaling of end-to-end distance R(E) radius of gyration R(G) and translational diffusivity D(T) with respect to the number of beads N(b) the Flory-Edwards exponent v was estimated as up to 1.0, which should be a really higher level compared to the case of the flexible neutral chains with self-avoiding walk in good solvent. Unlike the case of spherically averaged structure factor, scaling plots in that parallel to the first principal axis of gyration could not clearly be identified with a well defined exponent. With increasing screening effect, pronounced oscillations observed in the case of lower screening tend to smear out.
Keywords: DNA DIFFUSION; XANTHAN; MACROMOLECULES; RHEOLOGY; POLYMERS; MODEL; SHAPE